Chile Earthquake Of 2010 : Assessment of Industrial Facilities Around Concepci on. - Soules, J. G. (American Society of Civil Engineers, 2016)
This report contains the findings of an engineering team that assessed the effects of the 2010 Chile earthquake and tsunami on industrial facilities near Concepci on.